COMPARATIVE STUDY AND ANALYSIS OF BER OF CDMA FOR DIFFERENT MODULATION SCHEME - Kumar, Arun; Gupta, Dr. Manisha (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
With the increasing demand in wireless communication, it has become necessary to give better and efficient service to users by using better technique. This paper propose and analyse the bit error rate of CDMA, for different modulation schemes such as BPSK, QPSK and QAM. By Choosing a reliable modulation scheme and better filtration Technique the enhancement of the performance can be obtained in transmitter and receiver of CDMA system. Simulated result is shown to analyse and compare the performance of these systems by using additive white Gaussian noise channel (AWGN).Finally the different modulation schemes is compared on the basis of BER and best modulation scheme is determined. Â From analysis of three modulation techniques, the system could use more appropriate modulation technique to suit the channel quality, thus we can deliver the optimum and efficient data rate to mobile terminal.